A kinome-centered CRISPR-Cas9 screen identifies activated BRAF to modulate enzalutamide resistance with potential therapeutic implications in BRAF-mutated prostate cancer - Sander A. L. Palit; Jeroen van Dorp; Daniel Vis; Cor Lieftink; Simon Linder; Roderick Beijersbergen; Andries M. Bergman; Wilbert Zwart; Michiel S. van der Heijden (Scientific Reports, 2021)
Abstract Resistance to drugs targeting the androgen receptor (AR) signaling axis remains an important challenge in the treatment of prostate cancer patients. Activation of alternative growth pathways is one mechanism used by cancer cells to proliferate despite treatment, conferring drug resistance. Through a kinome-centered CRISPR-Cas9 screen in CWR-R1 prostate cancer cells, we identified activated BRAF signaling as a determinant for enzalutamide resistance. Combined pharmaceutical targeting of AR and MAPK signaling resulted in strong synergistic inhibition of cell proliferation. The association between BRAF activation and enzalutamide resistance was confirmed in two metastatic prostate cancer patients harboring activating mutations in the BRAF gene, as both patients were unresponsive to enzalutamide. Our findings suggest that co-targeting of the MAPK and AR pathways may be effective in patients with an activated MAPK pathway, particularly in patients harboring oncogenic BRAF mutations. These results warrant further investigation of the response to AR inhibitors in BRAF-mutated prostate tumors in clinical settings.